Cyclosporin A enhances neural precursor cell survival in mice through a calcineurin-independent pathway - Nadia Sachewsky; Jessica Hunt; Michael J. Cooke; Ashkan Azimi; Taraneh Zarin; Carween Miu; Molly S. Shoichet; Cindi M. Morshead (The Company of Biologists, 2014)
Cyclosporin A (CsA) has direct effects on neural stem and progenitor cells (together termed neural precursor cells; NPCs) in the adult central nervous system. Administration of CsA in vitro or in vivo promotes the survival of NPCs and expands the pools of NPCs in mice. Moreover, CsA administration is effective in promoting NPC activation, tissue repair and functional recovery in a mouse model of cortical stroke. The mechanism(s) by which CsA mediates this cell survival effect remains unknown. Herein, we examined both calcineurin-dependent and calcineurin-independent pathways through which CsA might mediate NPC survival. To examine calcineurin-dependent pathways, we utilized FK506 (Tacrolimus), an immunosuppressive molecule that inhibits calcineurin, as well as drugs that inhibit cyclophilin A-mediated activation of calcineurin. To evaluate the calcineurin-independent pathway, we utilized NIM811, a non-immunosuppressive CsA analog that functions independently of calcineurin by blocking mitochondrial permeability transition pore formation. We found that only NIM811 can entirely account for the pro-survival effects of CsA on NPCs. Indeed, blocking signaling pathways downstream of calcineurin activation using nNOS mice did not inhibit CsA-mediated cell survival, which supports the proposal that the effects are calcinuerin-independent. In vivo studies revealed that NIM811 administration mimics the pro-survival effects of CsA on NPCs and promotes functional recovery in a model of cortical stroke, identical to the effects seen with CsA administration. We conclude that CsA mediates its effect on NPC survival through calcineurin-independent inhibition of mitochondrial permeability transition pore formation and suggest that this pathway has potential therapeutic benefits for developing NPC-mediated cell replacement strategies.